Digital Complex for Modeling Processes in Electric Circuits with Protection and Automatic Devices - Oleksandr Ravlyk; Nazar Ravlyk (Energy Engineering and Control Systems)
The developed digital complex for modeling electromechanical and electromagnetic processes in electric circuits of any configuration with electromagnetic devices, control devices, synchronous and asynchronous motors including their control systems, protection devices and automation, allows us to carry out computation ranging from arc and voltage restoration of switches, to process of starting and restarting of electric motors. Digital Complex is designed for personal computers and computer systems in a Windows environment. Decision modeling tasks were performed by means of design schemes and their parameters created in a graphical environment. To form the majority of schemes of electro technical devices and protection systems a basic set of graphic elements, as well as unilateral and reciprocal links between them is provided. In addition to mutual inductances, models of the controlled dynamic and static connections by management functions developed for modeling electrical machines were used. The authors have developed the new effective methods for forming and solving equations for the significant performance and modeling in real time. The proposed complex is intended for engineering and scientific researches, and can be used for the formation of training systems for students and staff of the electric enterprises.